3D-printed weight holders design and testing in mouse models of spinal cord injury - De Vincentiis, Sara; Merighi, Francesca; Blümler, Peter; De La Ossa Guerra, Jose Gustavo; Di Caprio, Mariachiara; Onorati, Marco; Mainardi, Marco; Raffa, Vittoria; Carbone, Marina (Frontiers in Drug Delivery, 2024)
This paper details the comprehensive design and prototyping of a 3D-printed wearable device tailored for mouse models, addressing the need for non-invasive applications in spinal cord studies and therapeutic treatments. Our work was prompted by the increasing demand for wearable devices in preclinical research on freely behaving rodent models of spinal cord injury.Here, we present an innovative solution employing compliant 3D-printed structures for a stable device placement on the back of healthy and spinal cord-injured mice. In our specific trial, the device was represented by two magnets for the application of passive magnetic stimulation to the injury site. Indeed, this device was designed to be combined with the use of magnetic nanoparticles to render neurons or neural cells sensitive to an exogenous magnetic field, resulting in the stimulation of axon growth in response to a pulling force. We show different design iterations, emphasizing the challenges faced and the solutions proposed during the design process. The iterative design process involves multiple phases, from the Magnet Holder (MH) to the wearable device configurations. The latter include different approaches: a "Fitbit", a "Belt", a "Bib", and ultimately a "Cape".Each design iteration is accompanied by a testing protocol, involving healthy and injured mice, with qualitative assessments focusing on animal wellbeing. Follow-up lasted for at least 21 consecutive days, thus allowing accurate monitoring of animal welfare.The final "Cape" design is our best compromise between the need for a thin structure that should not hinder movements and the required resistance to maintain the structure at the correct positioning while withstanding biting and mechanical stress. The detailed account of the iterative design process and testing procedures provides valuable insights for researchers and practitioners engaged in the development of wearable devices for mice, particularly in the context of spinal cord studies and therapeutic treatments. Finally, in addition to describing the work done to design a 3D-printed wearable holder, we also outline some general guidelines for the design of wearable devices.